The paradoxical prognostic role of 1q21 Gain/Amplification in multiple myeloma: every coin has two sides. Issue 10 (23rd August 2020) - Xu, Jiadai; Xu, Tianhong; Yang, Yang; Wang, Wenjing; Li, Jing; Ren, Yuhong; Gu, Shiyang; Chen, Chen; Wei, Zheng; Zhuang, Jingli; Wang, Zhimei; Ji, Lili; et al.
Abstract: The prognostic value of 1q21 Gain/Amplification (1q21 Gain/Amp) in multiple myeloma (MM) has always been controversial. A total of 419 newly diagnosed MM patients were included in this retrospective study. The positive rate of 1q21 Gain/Amp was 48.6%. MM patients with 1q21 Gain/Amp were characterized as being in more advanced clinical stages and were more likely to be accompanied by del(13q14), t(4;14) or complex karyotypes (CKs) as well as with more severe anemia and worse renal function. In these patients, the percentage of complete remission (CR) or very good partial response (VGPR) was higher, however, in the early treatment period, the probability of progressive disease (PD) was also higher. No significant difference on progression free survival (PFS) and overall survival (OS) was showed between the group of 1q21Amp and 1q21Gain. The prognostic impact of 1q21 Gain/Amp on PFS of MM patients was heterogeneous and was in accordance with the accompanying parameters.